LANGUAGE INTERFERENCE OF BATAK ANGKOLA-MANDAILING LANGUAGE TOINDONESIAN: A CASESTUDY - Fauziah, Lita Rizki (2015)
This research aims to investigate the common characteristics of Indonesian pronunciation deviations made by undergraduate college students from BatakAngkola and observes the factors that contribute to the interference. The participants are two female BatakAngkola undergraduate students who have been living in Bandung for four years and are active speakers of Bahasa Indonesia and BatakAngkola-Mandailing language. To compare the results, four other participants who come from Jakarta and Bandung, have the same age and gender, and are not active speakers of any local languages are also recruited. Based on the pilot test conducted prior to the research, the phonemes that are investigated in the research are /e/, /ə/ and plosives (/b/, /d/, /g/, /k/, /t/, /p/). The data are collected through two types of assessment, which are a reading task, and pronunciation tests in the form of three word lists. By using software Praat, the deviations analysis and a further acoustic phonetic analysis of vowel and consonant duration are conducted. In general, there are two types of pronunciations deviations made by the participants: devoicing and allophonic shift that occurs between /ə/ into /e/ and /e/ into /ə/. The factors that contribute to the interference are speaker bilingualism background, language distant, anxiety, empathy and group solidarity. Keywords: Language interference, pronunciations, acoustic phonetics, BatakAngkola-Mandailing language. PenelitianinibertujuanuntukmenginvestigasikarakteristikumumdeviasipengucapanBahasa Indonesia yang dibuatolehmahasiswadariBatakAngkoladanmengobservasifaktor yang memengaruhiinterferensibahasatersebut.PartisipandalampenelitianiniadalahduamahasiswiBatakAngkola yang sudahtinggal di Bandung selamaempattahundanmerupakanpenuturaktifBahasa Indonesia danBahasaAngkola-Mandailing.Untukmembandingkanhasilnya, empatpartisipandari Jakarta dan Bandung yang mempunyaiusiadanjeniskelamin yang samasertabukanmerupakanpenuturaktifdaribahasalokalapapun, jugadirekrut. Berdasarkantes pilot yang dilakukansebelumpenelitian, fonem yang ditelitiadalah /e/, /ə/ danfonemplosif (/b/, /d/, /g/, /k/, /t/, /p/). Data diperolehmelaluiduatipepenilaian, yaitutesmembacadantespengucapandalambentukdaftar kata.DenganmenggunakanperangkatlunakPraat, analisisdeviasidananalisisfonetikakustikdurasivokaldankonsonandilakukan.Secaraumum, adaduajenisdeviasipengucapan yang dibuatolehpartisipan: devoicingdanperubahanalofonikantara /ə/ menjadi /e/ dan /e/ menjadi /ə/. Faktor yang memengaruhiinterferensitersebutadalahlatarbelakangbilingualismepenutur, jarakbahasa, anxiety, empatidansolidaritaskelompok. Kata Kunci: Interferensibahasa, pengucapan, fonetikakustik, BahasaBatakAngkola-Mandailing.